2005
DOI: 10.1175/jtech1791.1
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Calibration of Jason-1 and Envisat Altimeter Ku-Band Radar Cross Sections from Cross Comparison with TRMM Precipitation Radar Measurements

Abstract: One year of collocated, rain-free nadir Ku-band backscatter cross-section measurements from the Tropical Rainfall Mapping Mission (TRMM) precipitation radar (PR) and both Jason-1 and Envisat RA-2 altimeter measurements have been compiled to compare these three sources of Ku-band radar cross section. With the exception of a ϩ1.46 dB relative offset between Jason-1 and PR measurements and a Ϫ1.40 dB offset between Envisat and PR ones, all three Ku-band measurements compare very well in terms of dependencies upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Caudal et al [38] suggested that, compared with altimeters, in contrast with TOPEX, TRMM PR is biased by +1.2 dB whereas GEOdetic SATellite (GEOSAT) is biased by −0.7 dB. Tran et al [39] demonstrated that PR data (version 5) are lower in magnitude by approximately 1.46 dB than those of JASON-1 and larger by approximately 1.40 dB than ENVISAT measurements.…”
Section: A Satellite Datamentioning
confidence: 99%
“…Caudal et al [38] suggested that, compared with altimeters, in contrast with TOPEX, TRMM PR is biased by +1.2 dB whereas GEOdetic SATellite (GEOSAT) is biased by −0.7 dB. Tran et al [39] demonstrated that PR data (version 5) are lower in magnitude by approximately 1.46 dB than those of JASON-1 and larger by approximately 1.40 dB than ENVISAT measurements.…”
Section: A Satellite Datamentioning
confidence: 99%
“…To develop a new algorithm we start by observing trends using the combined collocated data from the six altimeters, a total of 30,733 data points. Differences in calibration between altimeters are small, of the order of tenths of meters for H s and tenths of decibels for σ 0 , and the greater number of data points makes trends in the data easier to observe (absolute calibrations of H s against buoy data are given in , and relative calibrations of σ 0 can be found in the work of, e.g., Callahan et al [1994] and Tran et al [2005]). Since different period parameters are useful for different applications ( T z is often used for ocean engineering, while T e is used for wave energy applications), we will consider how altimeter measurements relate to both T z and T e .…”
Section: Development Of the New Period Algorithmmentioning
confidence: 99%
“…As already demonstrated in previous analysis (e.g. [ 15 , 11 , 16 ]), our methodology is based on a co-location strategy. Here, we took advantage of the availability of an extensive collocation dataset between radar cross-section measurements and independent wind fields from the European Centre for Medium-Range Weather Forecasts (ECMWF) model surface wind analyses.…”
Section: Introductionmentioning
confidence: 99%